The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1177/104990910302000109
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual pain: A comparison of findings from survivors and hospice patients

Abstract: The article presents comparative research findings on the notion of "spiritual pain." The findings from interviews with hospice patients affirm the previously published, preliminary conceptualization of spiritual pain from interviews with survivors. However, while the survivor findings highlight the potential for spiritual pain associated with life after high-tech curative treatment, the hospice patient data emphasize the protectiveness of the hospice experience for deflecting the possibility of spiritual pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(110 citation statements)
references
References 22 publications
0
109
0
1
Order By: Relevance
“…Patient' relationships with their relatives improved and the value of material things declined, a development that was also noted in earlier studies carried out primarily with palliative and terminal patients (Adelbratt & Strang, 2000;McGrath, 2003). Yalom (1980) concludes that re-evaluation and reprioritization can be viewed as a way of gaining something positive from an external threat to life.…”
Section: Discussionmentioning
confidence: 77%
“…Patient' relationships with their relatives improved and the value of material things declined, a development that was also noted in earlier studies carried out primarily with palliative and terminal patients (Adelbratt & Strang, 2000;McGrath, 2003). Yalom (1980) concludes that re-evaluation and reprioritization can be viewed as a way of gaining something positive from an external threat to life.…”
Section: Discussionmentioning
confidence: 77%
“…It seems that existential suffering comes in many ways for these patients. In the literature there is currently no standard definition of existential pain, but generally, existential pain has been used as a metaphor for suffering (Saunders, 1988;McGrath, 2002McGrath, , 2003Musi, 2003;Strang et al, 2004). Strang et al (2004) concluded that it is obvious that existential pain is not a uniformly defined entity, as it obviously can be understood both as existential suffering and/or pain expressed in physical terms.…”
Section: Discussionmentioning
confidence: 99%
“…Although for some spirituality embraces religiosity (McGrath & Newell 200I), for most it is 'quintessentially of the ordinary' (McGrath 2002a) and refers to the sense they are making out of their life and illness experiences (McGrath 2002ba;2002c;2002d;2003a;2003b;2003c;McGrath & Newell 2002). However, the preliminary findings also posit 'connection' as an additional, but essential, dimension of the notion of spirituality.…”
Section: Introductionmentioning
confidence: 99%
“…The indications from the research are that individuals need a strong connection with life through family, friends, work and leisure, in order to deal with making sense of the challenge of serious illness. Such a connection can be threatened by a break with the normal or expected relationships and dissatisfaction with life through physical, identity, relational, and existential losses (McGrath, 2003a). When the disconnection is acutely painful (a subjective phenomenon depending on the individual), it is then experienced as 'spiritual pain', creating a void that challenges the individual's ability to make meaning from his or her existence (McGrath 2002b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation